The Role of Sharia Banking Towards Development of Micro, Small and Medium Enterprises (MSMEs) in Yogyakarta - Fathurrahman, Ayif; Fadilla, Jihan (Universitas Muhammadiyah Surakarta, 2019)
Purpose: This study aims to analyze the role of Islamic banking on the development of micro, small and medium enterprises (MSMEs) capital in Yogyakarta.Methodology: This test uses primary data obtained from the distribution of questionnaires with analysis tools using SPSS 20 software. The sampling method in this study used purposive sampling where 100samples were selected according to the research criteria. In this study using the sample criteria with microfinance customers in Islamic banking in Yogyakarta. The data analysis technique in this test is multiple regression analysis.Results: the results obtained in this test show that the variables of assistance, accessibility, and financing products have a positive and significant effect on capital development. However, the service variabledoes not have a positive and significant effect on MSMEs capital development in Yogyakarta. Thus,in order for the Islamic bank to improve service and customer satisfaction, it is necessary to increasefinancing, assistance, and accessibility. Even though in this study the service variable has no significan teffect, the related bank also needs to pay attention to service quality.